Case reportHailey-Hailey disease and contact hypersensitivity - Lis-Święty, Anna; Brzezińska-Wcisło, Ligia; Bergler-Czop, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Hailey-Hailey disease (HHD) is a genetically determined disorder of autosomal dominant mode of inheritance with high penetrance associated with mutations in the gene ATP2C1, which encodes the calcium ion dependent ATPase. Throughout all the skin, including pathologically unchanged skin, abnormal accumulation of Ca2+ by the keratinocytes in the granular layer is found. Skin lesions of an erythematous-exudative type (histologically: a vast, incomplete acantholysis above the basal layer of the epidermis) can be induced by various environmental factors: friction, high ambient temperature, increased sweating, UV radiation, and infectious, toxic and allergic agents. The aim is study was to drawing attention in some patients to the possible pathogenetic link between the hypersensitivity to various contact allergens and HHD. Three cases (48-year-old male, 32-year-old female, 42-year-old female) of HHD (medical history of two to nine years) coexisting with hypersensitivity to different contact allergens (nickel sulfate, cobalt chloride, Peruvian balsam, eugenol, aniline, benzocaine, metol) are presented in the paper. The introduction of appropriate preventive measures in patients with HHD and concomitant contact allergy can contribute to alleviating the symptoms of HHD.